2012
DOI: 10.1098/rspb.2012.0535
|View full text |Cite
|
Sign up to set email alerts
|

Long-term demographic consequences of a seed dispersal disruption

Abstract: The loss or decline of vertebrate frugivores can limit the regeneration of plants that depend on them. However, empirical evidence is showing that this is still very scarce, as functionally equivalent species may contribute to maintain the mutualistic interaction. Here, we investigated the long-term consequences of the extinction of frugivorous lizards on the population persistence of a Mediterranean relict shrub Cneorum tricoccon (Cneoraceae). We examined the demographic parameters among 26 insular and mainla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 29 publications
1
69
0
2
Order By: Relevance
“…Disruptions of mutualistic systems (pollination and seed dispersal) have often been documented, but their ecological implications have remained less extensively studied (Traveset and Richardson 2006;Rodríguez-Cabal et al 2011;Markl et al 2012;Traveset et al 2012). For example, mutualistic disruptions can induce cascading effects on biodiversity, but they remain quite unknown in an ecological context (Aslan et al 2013), especially on islands.…”
mentioning
confidence: 98%
“…Disruptions of mutualistic systems (pollination and seed dispersal) have often been documented, but their ecological implications have remained less extensively studied (Traveset and Richardson 2006;Rodríguez-Cabal et al 2011;Markl et al 2012;Traveset et al 2012). For example, mutualistic disruptions can induce cascading effects on biodiversity, but they remain quite unknown in an ecological context (Aslan et al 2013), especially on islands.…”
mentioning
confidence: 98%
“…Defaunation‐mediated downsizing of frugivorous vertebrates may trigger cascading effects with a myriad of consequences for demography (Cordeiro & Howe, ; Pérez‐Méndez et al., ; Traveset & Riera, ; Traveset et al., ) and genetics of plant populations (Calviño‐Cancela et al., ; Giombini et al, ; Pacheco & Simonetti, ; Pérez‐Méndez et al., ; Voigt et al., ). Here, we demonstrate that when seed dispersal interactions are disrupted (La Gomera) or functionally impaired (Tenerife), the genetic consequences may spread well beyond the local population scale.…”
Section: Discussionmentioning
confidence: 99%
“…[15], [17], [37], [38]). Even though seed dispersal disruptions are increasingly being reported from different ecosystems, few studies yet provide empirical evidence of the long-term costs of disruptions [39]. Traveset et al [39], however, showed that it can lead to species regression and in the long term, even to local extinctions.…”
Section: Discussionmentioning
confidence: 99%